2020
DOI: 10.7903/ijecs.1910
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution Adoption Technology Theory for E-Commerce

Abstract: The development of technology presents e-commerce as an alternative buying and selling place beside the offline shopping center. The growth of e-commerce globally confirms people's acceptance of e-commerce presence. Various theories of technology acceptance have been formulated to determine the factors that drive technology acceptance. The evolution of technology acceptance theory aims to overcome the problem of technology acceptance from various factors. The acceptance of e-commerce is interesting to learn as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
1
23
1
Order By: Relevance
“…This is an astonishing result, which departed from the findings of several studies in the literature [48], [49], [50], in which context-awareness was considered as a reliable predictor on behavioral intention. The reason for this inconsistent finding may be attributed to the roles of television and news in recent years [51].…”
Section: Theoretical Implicationscontrasting
confidence: 93%
“…This is an astonishing result, which departed from the findings of several studies in the literature [48], [49], [50], in which context-awareness was considered as a reliable predictor on behavioral intention. The reason for this inconsistent finding may be attributed to the roles of television and news in recent years [51].…”
Section: Theoretical Implicationscontrasting
confidence: 93%
“…Among the various factors identified in extant studies, Trust was found by [58] to appear early and usually at the inception of eCommerce process in the enterprise. Several other factors are technological and reflect the advancing nature of the technologies at play, with AI, Machine learning, IoT and similar others featuring in the discussions and practice.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…They theorized that the expectation of performance and the expectation of effort and social influence have significant relationships with the intention to use technologies. Recently, a series of studies have used these principles as a theoretical basis to explain the adoption of various technologies in different contexts including mobile payment (Al-Saedi et al, 2019), ecommerce (Haryanti and Subriadi, 2020), and mobile health (Dwivedi et al, 2020).…”
Section: Technology Acceptance Theoretical Backgroundmentioning
confidence: 99%